Institucionalização dos estudos de gênero na UFMA: uma análise da identidade feminista a partir da narrativa de vida - Morais, Adenilda Bertoldo Alves de (2016)
The feminist movement has generated feminist and gender studies undertaken by academic women in the universities of the western world from the decade of 1970. The objective of this research is to analyze, through the life stories of three academic, the relationship between "the personal" and "the institutional" in their narratives, highlighting their contributions to the institutionalization of gender studies. Narrative interviews were conducted (autobiographical) with three lecturer of the Federal University of Maranhão and built their biographies. They were used as analysis categories: Institution (Cornelius Castoriadis), feminist identity based on ManuelCastells, narrative (Sandra Jovchelovitch and Martin Bauer) and gender (Ana Coling). The analysis shows that even though they have won recognition from the academic community and society, the issue still remains in the ghetto in UFMA although institutionalized in the research groups.